Prevalencia y etiología de ametropías en pacientes geriátricos del centro gerontológico del cantón Babahoyo provincia de Los Ríos primer semestre 2018 - Mora Litardo, María Andrea (2018)
Introduction: The present investigative and descriptive study, like the professionals of the visual health and of the understanding of the state of the changes to ocular level that take place in this type of patients, as well as the changes of refraction, the examination analyzes transversally the prevalence of ametropias the vision of 80 geriatric patients and the etiologies of their pathologies Objective: To promote and determine the prevalence of different diseases according to their pathology detected in adult patients of the Gerontological Center of Babahoyo Canton Province of Los Ríos First Semester 2018. Recommended programs of specialized attention for this type of population, whose specific contribution is to give in the best possible way the help and quality of Vision both distant and close. Material and Methods: Visual acuity and retinoscopy tests were performed, and the results were analyzed through statistical analysis studies of central tendency and observation to characterize and compare the prevalence of alterations under the criteria of sex, age group and presence. of chronic ailments (diabetes, glaucoma, cataracts) with previous objective and then subjective methods, passing through the diagnosis the ametropia and the etiology presented in the geriatric patient, pigeon-holing and giving the appropriate treatment. Results:The visual acuity, Retinoscopy and ophthalmoscopy were screened for each older adult, detecting pathology and ametropias: (Myopia, Astigmatism, Hyperopia). Having as a result the prevalence of ametropia and etiology in pathology, having as a result of our study the following data. The Prevalence in Ametropias, in older men was detected 63.88%, while women 36.12%. And the frequency of prevalence in pathologies in the case of men was 64.47% and in women we have 35.53%. Astigmatism prevailed in refractive errors by 53% and myopia by 47%. Conclusions:A total of 80 elderly patients were studied in men 52 and 28 women, classifying them first in their medical problems and with information collected in the medical records of each older adult, according to the type of agreement with the presence of chronic diseases (cataract, glaucoma, diabetic retinopathy). The results indicated that the percentage of cataract was one (51.25%), and the highest rate of Ametropia was astigmatism one (52.77%). While myopia was (47.23%).